Vibration and oil analysis for monitoring problems related to water contamination in rolling - Gonçalves, Aparecido Carlos [UNESP]; Padovese, Linilson Rodrigues (My University, 2010)
Trying to reduce particle contamination in lubrication systems, industries of the whole world spend millions of dollars each year on the improvement of filtration technology. In this context, by controlling fluid cleanliness, some companies are able to reduce failures rates up to 85 percent. However, in some industries and environments, water is a contaminant more frequently encountered than solid particles, and it is often seen as the primary cause of component failure. Only one percent of water in oil is enough to reduce life expectancy of a journal bearing by 80 percent. For rolling bearing elements, the situation is worse because water destroys the oil film and, under the extreme temperatures and pressures generated in the load zone of a rolling bearing element, free and emulsified water can result in instantaneous flash-vaporization giving origin to erosive wear. This work studies the effect of water as lubricant contaminant in ball bearings, which simulates a situation that could actually occur in real systems. In a designed bench test, three basic lubricants of different viscosities were contaminated with different contents of water. The results regarding oil and vibration analysis are presented for different bearing speeds.
Keywords: Liquid contamination; Oil analysis; Rolling element bearing; Vibration analyis; Bearing speed; Bench tests; Component failures; Effect of water; Erosive wear; Extreme temperatures; Filtration technologies; Life expectancies; Load zones; Lubrication system; Oil films; Particle contamination; Real systems; Rolling bearing elements; Rolling Element Bearing; Solid particles; Water contamination; Water-in-oil; Work study; Ball bearings; Contamination; Emulsification; Journal bearings; Solid lubricants; Tribology; Water pollution; Vibration analysis